Halal Food as Da'wah on Tempe Entrepreneurship in Patipi Pasir, Teluk Patipi District, Fakfak Society, West Papua, Indonesia - Ikrima Laila Sabela; Ariana Suryorini; Lukmanul Hakim; Dedy Susanto (Jurnal Dakwah dan Komunikasi, 2026)
Purpose −   The concept of halal in Islam includes everything that is justified by the Shari'a, whether in terms of substance, processing process, or how to obtain it. In the framework of a halal lifestyle, the application of the halal principle is not solely related to consumption, but also becomes a form of spiritual awareness and obedience to religious teachings. The aim of this research is to examine people's understanding of the concept of halal food and analyze the impact of tempeh training as a means of da'wah in Patipi Pasir, Patipi Bay, Fakfak Regency, West Papua   Method −   The method used is descriptive qualitative with data collection techniques through in-depth interviews with the local community.   Findings −   The research results show that public understanding still focuses on normative aspects of sharia, without being accompanied by a comprehensive understanding of halalness in terms of materials, production processes and distribution. The lack of religious education is the cause of low halal literacy. Tempeh training has been proven to be effective in improving skills, encouraging food independence, and strengthening awareness of the importance of consuming halal products among the Patipi Pasir community. Da'wah integration and economic empowerment through local food is a potential strategy in building a halal lifestyle for the Patipi Pasir community. People who initially rarely consumed tempeh because access to the city was not easy have now started making tempeh independently. This is a good first step to create food independence for the Patipi Pasir community. Apart from being able to consume it every day, tempeh is also guaranteed to be halal. Food that is guaranteed to be halal can increase spiritual awareness, especially for the people of Patipi Pasir, Teluk Patipi, Fakfak Regency, West Papua.